Respuesta :

Answer:

Step-by-step explanation:

Sum = -14

Product = - 32

So, the factors = -16 , 2

When we add -16 +2 = -12 and when we multiply it is -32

w⁴ - 14w² - 32 =  w⁴ - 16w² + 2w² - 16 * 2

                      = w²(w² - 16) + 2(w² - 16)

                      = (w² - 16)(w² + 2)

                      = (w² - 4²)(w² + 2)

                      = (w + 4)(w - 4)(w² + 2)

Step-by-step explanation:

Replace w^2 with any other variable for eg: w^2=a

so that will make the equation:

a^2-14a-32

now factorize this equation and u can find the value of a

a^2-16a+2a-32

a(a-16)+2(a-16)

so factors= (a+2) (a-16)

since a was w^2 so replace them with w^2 and u got factors of the equation

you can also directly factorize the whole equation through middle term breaking

w^4-16w^2+2w^2-32

w^2(w^2-16)+2(w^2-16)

(w^2+2)(w^2-16)

you get the same answer